Levels of Intra-specific AFLP Diversity in Tuber-Bearing Potato Species with Different Breeding Systems and Ploidy Levels - Bryan, Glenn J.; McLean, Karen; Waugh, Robbie; Spooner, David M. (Frontiers in Genetics, 2017)
DNA-based marker analysis of plant genebank material has become a useful tool in the evaluation of levels of genetic diversity and for the informed use and maintenance of germplasm. In this study we quantify levels of Amplified Fragment Length Polymorphism (AFLP) in representative accessions of wild and cultivated potato species of differing geographic origin, ploidy, and breeding system. We generated 449 polymorphic AFLP fragments in 619 plants, representing multiple plants (16-23) from 17 accessions of 14 potato taxa as well as single plants sampled from available accessions (from 3 to 56) of the same 14 taxa. Intra-accession diversities were compared to those of a synthetic ‘taxon-wide’ population comprising a single individual from a variable number of available accessions of each sampled taxon. Results confirm the expected considerably lower levels of polymorphism within accessions of self-compatible as compared to self-incompatible taxa. We observed broadly similar levels of ‘taxon-wide’ polymorphism among self-compatible and self-incompatible species, with self-compatible taxa showing only slightly lower rates of polymorphism. The most diverse accessions were the two cultivated potato accessions examined, the least diverse being the Mexican allohexaploids Solanum demissum and S. iopetalum. Generally allopolyploid self-compatible accessions exhibited lower levels of diversity. Some purported self-incompatible accessions showed relatively low levels of marker diversity, similar to the more diverse self-compatible material surveyed. Our data indicate that for self-compatible species a single plant is highly representative of a genebank accession. The situation for self-incompatible taxa is less clear, and sampling strategies used will depend on the type of investigation. These results have important implications for those seeking novel trait variation (e.g. disease resistance) in gene banks as well as for the selection of individuals for genomics studies. We also show that AFLPs, despite having been largely replaced by other marker types, is highly suitable for the evaluation of within and between accession diversity in genebanks.